(untitled) (Psychology Travelogs, 2021)
The article presents the results of an empirical investigation of personal peculiarities of randomized groups of military personnel of volunteer battalions, mobilized servicemen and personnel, depending on the freedom of choice of risk. The methodological basis of the study was the scientific positions and conclusions of the natural–scientific theory concerning the regularities of higher nervous activity developed by V.M. Bekhterev, M.E.Vvedensky, I.I. Pavlov, I.M. Sechenov etc., ideas and provisions concerning psychological theory of personality (B.G. Ananiev, K.K. Platonov, S.L. Rubinstein, etc.), psychological theory of activity (O.M. Leontiev, B.F. Lomov, S.D. Maksimenko, D.N. Uznadze, etc.), practical psychology and psycho diagnostics (L.F. Burlachuk, K.M. Gurevich, V.S. Kompanets, R. Lazarus, M.D. Levitov, N.I. Nayenko, G. Selye, S.I. Yakovenko, etc.), psycho corrections (P.K. Anokhin, O.A. Konopkin, K.Rudestam, O.V. Timchenko, Ye.M. Potapchuk), theoretical and practical provisions of human psychology (A. Maslow, K. Rogers, etc.), as well as theoretical principles of management of personality development in a social environment (A.F. Bondarenko, T.S.Yatsenko). To solve the problems posed in the research, the author was selected and a number of techniques were used that included the following methods: adapted versions of tests for MMPL 16 PF (FOO), multi-level test questionnaire "Adaptability", questionnaire of general health, (GHQ-28), Personal Health Questionnaire by G. Eysenck (EPI), the method of diagnostics of character logical features G. Shmyshek - K. Leonhard, patoharakterologicheskii questionnaire A.E. Lichko, the pollster of traumatic stress under the editorship I.O. Kotenko, T. Liri (interpersonal relations), a modified social-psychological questionnaire (Joint Study Project 1993) - a "questionnaire of dangers" and socio-psychological and sociometric methods that allow to evaluate interpersonal relationships, standardized interviews, individual psycho diagnostic conversation, observation, analysis of independent characteristics. Excel 2010 spreadsheets (MS Windows) have been used as a database structure. The statistical analysis is carried out in the program Statistica 10.0 (Stat Soft) with the help of parametric and nonparametric criteria. The hypothesis of the study is to assume that excessively reinforced individual personality traits will most clearly be manifested by the freedom of choice of a soldier of risk and have different dynamics and mechanisms for responding to specific psychogenic influences of armed conflict. The use of adequate psychological aids to personality disorders will significantly affect the reduction of anxiety, frustration, aggressiveness on the results of professional activity and health of the staff of the armed forces.